2016
DOI: 10.1038/srep38573
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Sulfoxide-Induced Single Turn Peptide α-Helicity

Abstract: Inducing α-helicity through side-chain cross-linking is a strategy that has been pursued to improve peptide conformational rigidity and bio-availability. Here we describe the preparation of small peptides tethered to chiral sulfoxide-containing macrocyclic rings. Furthermore, a study of structure-activity relationships (SARs) disclosed properties with respect to ring size, sulfur position, oxidation state, and stereochemistry that show a propensity to induce α-helicity. Supporting data include circular dichroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…The peptide epimers' conformational preferences were then tested by CD spectroscopy. As shown in Figure C, peptide 1R with longer retention time on HPLC showed more higher helical contents than peptide 1S , which is in agreement with our previous work, demonstrating that the CIH concept could be translated into an all‐hydrocarbon tethered peptide. Notably, the α‐methyl group in the olefinic amino acid is not necessary for constructing CIH helical peptides .…”
Section: Results and Disscussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The peptide epimers' conformational preferences were then tested by CD spectroscopy. As shown in Figure C, peptide 1R with longer retention time on HPLC showed more higher helical contents than peptide 1S , which is in agreement with our previous work, demonstrating that the CIH concept could be translated into an all‐hydrocarbon tethered peptide. Notably, the α‐methyl group in the olefinic amino acid is not necessary for constructing CIH helical peptides .…”
Section: Results and Disscussionsupporting
confidence: 91%
“…Recently, our group developed a chirality induced helicity (CIH) strategy by which a precisely positioned chiral center on the tether could dominate the backbone peptides' helicity, with improved cell permeability and binding affinity towards mammal double minute 2 (MDM2) and estrogen receptor alpha (ERα) . This strategy could also be extended to sulfilimide chiral center and sulfoxide chiral center, which provide a valuable modifiable site on the tether . Meanwhile, Moore et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al. calculated a N−C−C−S dihedral angle of approximately −66° when the sulfoxide was pointed away from the helix in the R configuration, whereas in the S configuration the sulfoxide oxygen pointed towards the peptide, causing a steric clash that led to an increase in the dihedral angle to −81° . As we were unable to separate the diasteromeric sulfoxide species, we might have enhanced helicity for only one diastereomer.…”
Section: Resultsmentioning
confidence: 87%
“…on short single‐turn helical macrocycles. Using shorter hydrocarbon linkers, they also observed a reduction in helicity for singly oxidized thioether‐crosslinked peptides to both a sulfoxide and a sulfone . Furthermore, it was observed that only one sulfoxide epimer enhanced the helicity, whereas the other disrupted helicity.…”
Section: Resultsmentioning
confidence: 95%